How non-ferromagnetic Mn enhances the magnetization of SmCo7 based alloys. Issue 9 (25th February 2020) - Guo, Kai; Lu, Hao; Mao, Fei; Liu, Dong; Tang, Fawei; Wang, Haibin; Song, Xiaoyan
Abstract : It was discovered that the non-ferromagnetic element Mn enhances magnetization through modulating the magnetic structure. By tailoring the Mn content and nanostructuring, the prepared SmCo7− x Mn x alloy achieved good comprehensive magnetic properties. Abstract : This work was focused on the effects of Mn doping on the phase stability and magnetic performance of SmCo7 based alloys. Particularly, the role of Mn in the improvement of the magnetization of the SmCo7 matrix, as well as its mechanisms, was examined in detail. The metastable SmCo7 single phase was well stabilized by the appropriate content of Mn doping and nanostructuring of the alloy. It was discovered that the non-ferromagnetic element Mn can enhance magnetization effectively. By tailoring the Mn content and nanostructuring, the prepared SmCo7− x Mn x alloy achieved good comprehensive magnetic properties. The mechanisms for the magnetization enhancement by Mn and the coupled effect of Mn doping and nanostructuring on the magnetic properties were proposed based on the characterization of magnetic structures and the model calculations of magnetic moments.